Per la priorità di Antonio Meucci nell'invenzione del telefono - Luigi, Respighi (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2008)
April 2008 marks the bicentenary of the birth of Antonio Meucci (Florence, 13 April 1808 - New York, 18 October 1889), universally recognised as the inventor of the telephone and one of the outstanding figures representing the creative and scientific achievements of Florence. The Faculty of Engineering of the University of Florence has taken the initiative of celebrating the anniversary by obtaining permission to establish a National Committee from the Ministry for the Cultural Heritage.